2022
DOI: 10.1039/d2cp02223k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ionic liquids on the chain dynamics and enthalpy relaxation of poly(methyl methacrylate)

Abstract: Imidazolium ionic liquids (ILs) with various alkyl chain length on the cations ([Cnmim]+, n = 2, 4 and 8) and different combined anions ([TFSI]− and [PF6]−) were blended with poly(methyl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…5(g), a wide peak observed in the range of 260–1000 cm −1 can be attributed to the stretching vibration of C–O in PMMA, while the carbonyl stretching vibration peak of PMMA is observed at 1730 cm −1 , indicating the presence of methyl formate units in PMMA. 41,42 The peaks at 2930 cm −1 and 2860 cm −1 correspond to the symmetric and asymmetric stretching vibrations of a methyl group, respectively, and prove the existence of the methyl group in PMMA. 43 In addition, the CC stretching peak can be seen in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…5(g), a wide peak observed in the range of 260–1000 cm −1 can be attributed to the stretching vibration of C–O in PMMA, while the carbonyl stretching vibration peak of PMMA is observed at 1730 cm −1 , indicating the presence of methyl formate units in PMMA. 41,42 The peaks at 2930 cm −1 and 2860 cm −1 correspond to the symmetric and asymmetric stretching vibrations of a methyl group, respectively, and prove the existence of the methyl group in PMMA. 43 In addition, the CC stretching peak can be seen in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Besides, ILs have a plasticizing effect on polymeric materials 14,18–22 . It was found that the T g of PMMA decreases with increasing the amounts of ILs 20,23 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Other studies reported changes in the conformation of polyethylene oxide (PEO) and polymethyl methacrylate (PMMA) polymer chains due to the interaction with ILs. [14][15][16][17] Besides, ILs have a plasticizing effect on polymeric materials. 14,[18][19][20][21][22] It was found that the T g of PMMA decreases with increasing the amounts of ILs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations